Phage-choline Kinase Inhibitor Combination to Control Pseudomonas aeruginosa: A Promising Combo - Khalifa, Moad; Few, Ling L.; Too, Wei C. S. (Mini Reviews in Medicinal Chemistry, 2022)
Background: Pseudomonas aeruginosa is one of the most prevalent opportunistic pathogens in humans that has thrived and proved to be difficult to control in this “post-antibiotic era.” Antibiotic alternatives are necessary for fighting against this resilient bacterium. Even though phages might not be “the wonder drug” that solves everything, they still provide a viable option to combat P. aeruginosa and curb the threat it imposes. Main Findings: The combination of antibiotics with phages, however, poses a propitious treatment option for P. aeruginosa. Choline kinase (ChoK) is the enzyme that synthesizes phosphorylcholine subsequently incorporated into lipopolysaccharide located at the outer membrane of gram-negative bacteria. Recently, inhibition of ChoKs has been proposed as a promising antibacterial strategy. Successful docking of Hemicholinium-3, a choline kinase inhibitor, to the model structure of P. aeruginosa ChoK also supports the use of this inhibitor or its derivatives to inhibit the growth of this microorganism. Conclusion: Therefore, the combination of the novel antimicrobial “choline kinase inhibitors (ChoKIs)” with a phage cocktail or synthetic phages as a potential treatment for P. aeruginosa infection has been proposed.
Keywords: antibiotic resistance